Enterovirus 75 encephalitis in children, Southern India - Penny, Lewthwaite; David, Perera; Mong How, Ooi; Anna, Last; Ravi, Kumar; Anita, Desai; Begum, Ashia; Vasanthapuram, Ravi; M. Veera, Shankar; Phaik Hooi, Tio; Mary Jane, Cardosa; Tom, Solomon (NationalCenter for Biotechnology Information, U.S. National Library of Medicine, 2010)
Recent outbreaks of enterovirus in Southeast Asia emphasize difficulties in diagnosis of this infection. To address this issue, we report 5 (4.7%) children infected with enterovirus 75 among 106 children with acute encephalitis syndrome during 2005–2007 in southern India. Throat swab specimens may be useful for diagnosis of enterovirus 75 infection.